The Effect of Bleaching Program, Awareness and Sanctions on Compliance of Motor Vehicle Taxpayers in Cirebon City - Rafa Faridah, Nur; Qomalasari, Zahwa; Firasati, Aoliyah (DINASTI RESEARCH, 2025)
This study aims to know the impact of bleaching program, awareness and sanctions on the compliance of motor vehicle taxpayers in the city of Cirebon. This quantitative study used multiple linear regression analysis with SPSS 26. Four hundred respondents were selected at random and given a questionnaire. The participants in this study were individuals who owned a registered motor vehicle at the SAMSAT Cirebon City. The findings showed that the only variable that significant and positive affected taxpayer compliance was awareness. Meanwhile, there was no visible impact from the sanctions and bleaching program factors. In addition to offering guidance for future academics who wish to expand their research by incorporating other, more varied variables, it is hoped that the findings of this study will be taken into account by relevant institutions when they formulate policies to improve taxpayer compliance.